Fighting against Cardiovascular Diseases in 21st Century by Healthy Life-Style and Healthy Diet - Haq, M Maksumul; Amin, Md Nurul (Ibrahim Cardiac Medical Journal, 2011)
Ibrahim Card Med J 2011; 1(1):5-8